Surface-coated positive electrode material, its manufacturing method, and lithium-ion battery

JP7640758B2Active Publication Date: 2025-03-05BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023580763
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-05
Publication Date
2025-03-05
Estimated Expiration
2043-06-05

AI Technical Summary

Benefits of technology

【0010】 上記の技術案によれば、本発明による表面被覆正極材料、その製造方法及び使用、並びに、リチウムイオン電池には、以下の有益な効果が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640758000007
    Figure 0007640758000007
  • Figure 0007640758000008
    Figure 0007640758000008
  • Figure 0007640758000009
    Figure 0007640758000009
Patent Text Reader

Abstract

The present invention relates to the field of lithium ion batteries and discloses a surface-coated positive electrode material, a manufacturing method thereof, and a lithium ion battery. The positive electrode material includes a substrate and a coating layer coated on the substrate. XRD measurement of the coating layer shows that a characteristic peak at 2θ of 31° to 35° shows a bimodal distribution, and the peak intensity I of a minor peak in the bimodal distribution is 1. b and the peak intensity of the main peak I a Comparison with I b / I a is 0.8 to 1. The surface-coated positive electrode material has high ionic and electronic conductivity, and can increase the diffusion rate of ions and electrons in the positive electrode material, thereby improving the rate characteristics of a lithium-ion battery containing the positive electrode material. In addition, the surface-coated positive electrode material having the above-mentioned specific coating layer can avoid contact corrosion between the positive electrode material and the electrolyte, and can improve the cycle stability of a lithium-ion battery containing the positive electrode material. Furthermore, the thermal stability of the surface-coated positive electrode material having the above-mentioned specific coating layer is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of Chinese patent application No. 202210770763.9, filed on Jun. 30, 2022, the contents of which are incorporated herein by reference.

[0002] The present invention relates to the technical field of lithium ion batteries, in particular to a surface-coated positive electrode material, a method for producing the same, and a lithium ion battery. [Background technology]

[0003] With the rapid development of the power battery market, the requirements for energy density and safety of lithium-ion batteries are increasing. In recent years, in order to further increase the energy density of lithium-ion batteries and reduce costs, the trend has been to increase the nickel content and decrease the cobalt content. However, as the nickel content increases, the thermal stability of the material deteriorates, and the safety during battery use decreases. In addition, tetravalent nickel generated during charging and discharging is highly oxidizing and easily reacts with the electrolyte, which causes deterioration of cycle characteristics and battery swelling. Therefore, in order to further improve the thermal stability and cycle stability of the material, coating modification technology has been widely applied to various positive electrode materials. CN109065875A discloses a method for producing a coated high-nickel multi-element material, which uses materials such as ZrO2, TiO2, Al2O3, and MgO as coating agents to reduce side reactions between the positive electrode and the electrolyte and improve battery properties, but the coating agents used in this method are all inert materials and cannot participate in the transport of ions and electrons, and there is no improvement in the thermal stability of the high-nickel material. Summary of the Invention [Problem to be solved by the invention]

[0004] The object of the present invention is to provide a surface-coated positive electrode material, a manufacturing method thereof, and a lithium ion battery in order to solve the problems existing in the prior art. The surface-coated positive electrode material includes a substrate and a coating layer coated on the substrate. The coating layer is subjected to XRD measurement, and the characteristic peak at 2θ of 31° to 35° shows a bimodal distribution, and the bimodal distribution has a specific ratio of peak intensity between the main peak and the sub-peak, so that the surface-coated positive electrode material has high ionic and electronic conductivity, and can increase the diffusion rate of ions and electrons in the positive electrode material and improve the rate characteristics of a lithium ion battery including the positive electrode material. In addition, the surface-coated positive electrode material having the specific coating layer can avoid contact corrosion between the positive electrode material and the electrolyte and improve the cycle stability of a lithium ion battery including the positive electrode material. In addition, the thermal stability of the surface-coated positive electrode material having the specific coating layer is significantly improved. [Means for solving the problem]

[0005] In order to achieve the above object, the first aspect of the present invention comprises: A substrate and a coating layer coated on a surface of the substrate, The coating layer was subjected to XRD measurement. The characteristic peak at 2θ of 31° to 35° exhibited a bimodal distribution, and the sub-peak intensity I b and the peak intensity of the main peak I a Comparison with I b / I a is 0.8 to 1.

[0006] A second aspect of the present invention is Lithium source, La source, any N 1 source, N 2 source, N 3 Source, any N 4 S1, subjecting the source to a first mixture to obtain a first mixture, sintering and crushing the first mixture to obtain a coating; and (S2) subjecting the coating agent and the base material of the cathode material to a second mixing to obtain a second mixture, and subjecting the second mixture to a first heat treatment to obtain the surface-coated cathode material.

[0007] A third aspect of the present invention is Lithium source, La source, any N 1 source, N 2 source, N 3 Source, any N 4 and subjecting a source of the cathode material and a substrate of the cathode material to a third mixture to obtain a third mixture, and performing a second heat treatment to obtain the surface-coated cathode material.

[0008] A fourth aspect of the present invention provides a surface-coated positive electrode material produced by the above-mentioned production method.

[0009] A fifth aspect of the present invention provides a lithium ion battery comprising the above-mentioned surface-coated positive electrode material. Effect of the Invention

[0010] According to the above technical solution, the surface-coated positive electrode material, its preparation method and use, and the lithium ion battery according to the present invention can achieve the following beneficial effects:

[0011] (1) The surface-coated positive electrode material according to the present invention includes a substrate and a coating layer coated on the substrate, and the coating layer is subjected to XRD measurement. The characteristic peaks at 2θ of 31° to 35° show a bimodal distribution, and the bimodal distribution has a ratio of a specific main peak intensity to a specific sub-peak intensity, so that the surface-coated positive electrode material has high ionic and electronic conductivity, and can increase the diffusion rate of ions and electrons in the positive electrode material and improve the rate characteristics of a lithium ion battery containing the positive electrode material. In addition, the surface-coated positive electrode material having the specific coating layer can avoid contact corrosion between the positive electrode material and the electrolyte and improve the cycle stability of a lithium ion battery containing the positive electrode material. Furthermore, the thermal stability of the surface-coated positive electrode material having the specific coating layer is significantly improved.

[0012] (2) In the surface-coated positive electrode material according to the present invention, the substrate and the coating layer have a specific composition, so that the positive electrode material can have electrochemical activity for deintercalating lithium ions, and the coating material used has a higher lithium ion transport capacity and at the same time a lower oxygen hole formation energy, which can improve the electronic conductivity and increase the diffusion rate of ions and electrons in the positive electrode material, thereby significantly improving the rate characteristics of a lithium ion battery containing the positive electrode material. On the other hand, in the present invention, the coating layer has a specific composition, so that the side reaction at the interface between the surface of the positive electrode material particles and the electrolyte can be effectively suppressed, and the cycle stability of a lithium ion battery containing the positive electrode material can be significantly improved, and the thermal stability of the positive electrode material can be effectively improved.

[0013] (3) The method for producing the positive electrode material according to the present invention has a simple process, is free from contamination by dopant elements, is simple in the introduction method of the coating layer, has a small amount of use, has no special requirements for the heat treatment atmosphere, has low production costs, and is suitable for large-scale industrial production. [Brief description of the drawings]

[0014] [Figure 1]FIG. 2 is an XRD phase diagram of the coating material in Example 1. [Diagram 2] FIG. 2 is an XRD phase diagram of the positive electrode material after coating in Example 1. [Diagram 3] FIG. 2 is a 0.1C charge / discharge curve diagram of the half cells prepared in Comparative Example 1, Example 1, and Example 4. [Figure 4] FIG. 2 is a 0.1C charge / discharge curve diagram of the half cells prepared in Comparative Example 2, Example 2, and Example 3. [Diagram 5] FIG. 2 is a DSC curve diagram of Comparative Example 1, Example 1, and Example 4. [Figure 6] FIG. 2 is a DSC curve diagram of Comparative Example 2, Example 2, and Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The range endpoints and any values ​​disclosed herein should be understood not to be limited to the exact range or value, but to include values ​​close to these ranges or values. In the case of numerical ranges, the values ​​between the endpoints of each range, between the endpoints of each range and the individual point values, and between the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which numerical ranges should be considered as specifically disclosed herein.

[0016] A first aspect of the present invention includes a substrate and a coating layer coated on a surface of the substrate, The coating layer was subjected to XRD measurement. The characteristic peak at 2θ of 31° to 35° exhibited a bimodal distribution, and the peak intensity I b and the peak intensity of the main peak I a Comparison with I b / I a is 0.8 to 1.

[0017] In the present invention, the surface-coated positive electrode material includes a substrate and a coating layer coated on the surface of the substrate. XRD measurement of the coating layer shows that a characteristic peak at 2θ of 31° to 35° exhibits a bimodal distribution, and the bimodal distribution has a specific peak intensity ratio between a main peak and a sub-peak. As a result, the surface-coated positive electrode material has high ionic and electronic conductivity, and can increase the diffusion rate of ions and electrons in the positive electrode material and improve the rate characteristics of a lithium-ion battery including the positive electrode material.

[0018] Furthermore, the surface-coated positive electrode material having the specific coating layer can avoid contact corrosion between the positive electrode material and the electrolyte, and improve the cycle stability of the lithium-ion battery containing the positive electrode material. Furthermore, the thermal stability of the surface-coated positive electrode material having the specific coating layer is significantly improved. In the present invention, the peak intensity I of the minor peak in the bimodal distribution b and the peak intensity of the main peak I a are measured by XRD, respectively.

[0019] Furthermore, I b / I a is 0.97 to 1.

[0020] According to the present invention, the peak intensity of the characteristic peak (003) corresponding to the (003) crystal plane obtained by XRD measurement of the substrate is I (003) Then, 0.01%≦I a / I (003) ×100%≦3.5%.

[0021] In the present invention, in the coating layer, the peak intensity I of the main peak in the bimodal distribution of characteristic peaks at 31 ° to 35 ° is a and the peak intensity I of the characteristic peak (003) corresponding to the (003) crystal plane of the substrate. (003) Comparison with I a / I (003)When satisfies the above range, the thermal stability of the positive electrode material can be improved, the temperature corresponding to the heat release peak measured by DSC on the positive electrode material can be increased, and the lithium ion battery including the positive electrode material can have higher safety.

[0022] In the present invention, the peak intensity I of the characteristic peak (003) corresponding to the (003) crystal plane of the substrate is (003) is measured by XRD.

[0023] Furthermore, 0.08%≦I a / I (003) ×100%≦3.1%.

[0024] According to the present invention, the substrate was subjected to XRD measurement, and the peak area of ​​the characteristic peak (003) corresponding to the (003) crystal plane was determined as A (003) The coating layer was subjected to XRD measurement. The peak area of ​​the main peak in the characteristic bimodal distribution where 2θ is 31° to 35° was determined as A a Then, 0.01%≦A a / A (003) ×100%≦6%.

[0025] In the present invention, the area of ​​the main peak in the bimodal distribution of characteristic peaks at 31 ° to 35 ° in the coating layer is A a The peak area of ​​the characteristic peak (003) corresponding to the (003) crystal plane of the substrate is A (003) Then, the ratio A a / A (003) When satisfies the above range, the thermal stability of the positive electrode material can be improved, the temperature corresponding to the heat release peak measured by DSC on the positive electrode material can be increased, and the lithium ion battery including the positive electrode material can have higher safety.

[0026] In the present invention, the main peak area A in the bimodal distribution of the characteristic peaks at 31 ° to 35 ° of the coating layer a , and the peak area A of the characteristic peak (003) corresponding to the (003) crystal plane of the substrate (003) is measured by XRD.

[0027] Furthermore, 0.5% ≤ A a / A (003) × 100% ≤ 4.8%. According to the present invention, the base material has a composition represented by Formula I, Li 1+a Ni x Co y Mn z M k O2 Formula I (However, -0.05 ≤ a ≤ 0.5, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ k ≤ 0.06, 0 < x + y + z + k ≤ 1, and M is at least one element selected from Ga, Sc, In, Y, Ce, Co, La, Cr, Mo, Mn, Fe, Hf, Zr, W, Nb, Sm, and Al.) The coating layer has a composition represented by Formula II, Li α-β-γ-δ La β N 1 γ N 2 δ N 3 1-λ N 4 λ O3 Formula II (However, 0.7 < α < 1.5, 0.2 < β < 1, 0 ≤ γ < 0.5, 0 ≤ δ < 0.5, 0 ≤ λ < 0.5, and N 1 is at least one element selected from Y, Nd, Pr, Ce, Sm, and Sc, N 2 is at least one element selected from Sr, Ca, Mg, Si, Ge, and Ru, N 3 is at least one element selected from Ni, Mn, and Co, N 4 is at least one element selected from Cr, Al, V, Nb, Zr, Ti, and Fe.)

[0028] In the present invention, the substrate and coating layer of the surface-coated positive electrode material have a specific composition, so that the positive electrode material can have electrochemical activity for deintercalating lithium ions, and the coating material used has a higher lithium ion transport capacity and at the same time has a lower oxygen hole formation energy, which can improve the electronic conductivity, and can increase the diffusion rate of ions and electrons in the positive electrode material, thereby significantly improving the rate characteristics of a lithium ion battery containing the positive electrode material. On the other hand, in the present invention, the coating layer has a specific composition, so that the side reaction at the interface between the surface of the positive electrode material particles and the electrolyte can be effectively suppressed, and the cycle stability of a lithium ion battery containing the positive electrode material can be significantly improved, and the thermal stability of the positive electrode material can be effectively improved.

[0029] Furthermore, in formula I, M is at least one element selected from Ce, Co, La, Cr, Mo, Y, Zr, W, Nb, and Al.

[0030] Furthermore, in formula II, 0.9<α<1.3, 0.35<β<0.7, 0.04≦γ<0.4, 0<δ<0.3, and 0≦λ<0.46.

[0031] Further, in formula II, N 1 is at least one element selected from Nd, Pr, Ce, Sm, and Sc.

[0032] Further, in formula II, N 2 is at least one element selected from Sr, Ca, Mg, Si, and Ru.

[0033] Further, in formula II, N 3 is selected from Ni and / or Mn.

[0034] Further, in formula II, N 4 is at least one element selected from Cr, Al, Nb, Zr, Ti, and Fe.

[0035] According to the present invention, the content of the coating layer is 0.05 to 4 wt % based on the total weight of the base material.

[0036] In the present invention, when the content of the coating layer is within the above range, the surface of the positive electrode material has a uniform coating layer, so that the surface of the positive electrode material has high ion transport properties and electron transport properties, and a lithium ion battery including the positive electrode material can have excellent electrochemical properties.

[0037] Furthermore, the content of the coating layer is 0.5 to 3.6 wt % based on the total weight of the base material. According to the present invention, the average particle diameter D of the surface-coated positive electrode material 50 is 2 to 17 μm.

[0038] Furthermore, the average particle diameter D of the surface-coated positive electrode material 50 is 3 to 12 μm.

[0039] According to the invention, the electronic conductivity of the coating layer is 1×10 -5 S / cm~8×10 -3 S / cm. In the present invention, when the electronic conductivity of the coating layer satisfies the above range, the electron transport ability is high, and an electronically conductive layer is formed on the surface of the positive electrode material, thereby imparting excellent electrochemical properties to a lithium ion battery containing the positive electrode material.

[0040] Furthermore, the electronic conductivity of the coating layer is 1.8×10 -5 S / cm~7.2×10 -3 S / cm. According to the present invention, the ionic conductivity of the coating layer is 1×10 -6 S / cm~6×10 -4 S / cm.

[0041] In the present invention, when the ionic conductivity of the coating layer satisfies the above range, the ion transport properties are high, and an ionic conductive layer is formed on the surface of the positive electrode material, thereby imparting excellent electrochemical properties to a lithium ion battery including the positive electrode material.

[0042] Furthermore, the ionic conductivity of the coating layer is 3×10 -6 S / cm~5×10 -4 S / cm.

[0043] According to the present invention, the oxygen hole formation energy of the coating layer is −2 eV to 4.5 eV.

[0044] In the present invention, when the oxygen hole formation energy of the coating layer satisfies the above range, the electron transport ability is high, an electronic conductive layer is formed on the surface of the positive electrode material, and excellent electrochemical properties are imparted to a lithium ion battery containing the positive electrode material.

[0045] Furthermore, the oxygen hole formation energy of the coating layer is −1.8 eV to 4 eV.

[0046] According to the present invention, when the temperature corresponding to the heat dissipation peak in the DSC measurement of the surface-coated positive electrode material is T1 and the temperature corresponding to the heat dissipation peak in the DSC measurement of the base material is T0, T1-T0 is 3 to 15°C.

[0047] In the present invention, when the difference in temperature corresponding to the heat dissipation peak in DSC measurement of the surface-coated positive electrode material and the substrate satisfies the above-mentioned range, the thermal stability of the positive electrode material can be significantly improved, and a lithium ion battery including the positive electrode material can be made highly safe.

[0048] Furthermore, T1-T0 is 3 to 14°C.

[0049] A second aspect of the present invention is Lithium source, La source, any N 1 Source, any N 2 source, N 3 Source, any N 4 S1, subjecting the source to a first mixing to obtain a first mixture, and subjecting the first mixture to a first sintering to crush and obtain a coating; and step S2 of subjecting the coating agent and the base material of the positive electrode material to a second mixing to obtain a second mixture, and subjecting the second mixture to a second sintering to obtain the surface-coated positive electrode material.

[0050] In the present invention, a lithium source, a La source, and an optional N 1 Source, any N 2 source, N 3 Source, any N 4 A coating agent obtained by sintering a first mixture containing a source is mixed with a substrate of a cathode material and heat-treated to obtain a surface-coated cathode material comprising a substrate and a coating layer provided on a surface of the substrate, and the coating layer has the characteristics described in the first aspect of the present invention. Specifically, in the surface-coated cathode material produced by the production method according to the present invention, XRD measurement of the coating layer shows that a characteristic peak at 2θ of 31° to 35° exhibits a bimodal distribution, and the bimodal distribution has a specific peak intensity ratio between a main peak and a sub-peak. As a result, the surface-coated cathode material has high ionic conductivity and electronic conductivity, and can increase the diffusion rate of ions and electrons in the cathode material and significantly improve the rate characteristics of a lithium-ion battery containing the cathode material.

[0051] Furthermore, the surface-coated positive electrode material having the specific coating layer can avoid contact corrosion between the positive electrode material and the electrolyte, and improve the cycle stability of the lithium-ion battery containing the positive electrode material. Furthermore, the thermal stability of the surface-coated positive electrode material having the specific coating layer is significantly improved.

[0052] In addition, the manufacturing method has a simple process, is free from contamination by dopant elements, has a simple method for introducing the coating layer, requires a small amount of material, has no special requirements for the heat treatment atmosphere, has low production costs, and is suitable for large-scale industrial production.

[0053] According to the present invention, the lithium source, the La source, the N 1 Source, N 2 Source, N 3 Source, N 4The amount of sources used is n(Li):n(La):n(N 1 ):n(N 2 ):n(N 3 ):n(N 4 ) such that (α-β-γ-δ):β:γ:δ:(1-λ):λ, with 0.7<α<1.5, 0.2<β<1, 0≦γ<0.5, 0≦δ<0.5, and 0≦λ<0.5.

[0054] Furthermore, 0.9<α<1.3, 0.35<β<0.7, 0.04≦γ<0.4, 0<δ<0.3, and 0≦λ<0.46.

[0055] According to the present invention, the amount of the coating agent used is 0.05 to 4 wt %, preferably 0.1 to 3.6 wt %, based on the total weight of the base material of the positive electrode material.

[0056] According to the present invention, the N 1 The source is selected from compounds containing at least one of the elements Y, Nd, Pr, Ce, Sm, and Sc.

[0057] According to the present invention, the N 2 The source is selected from compounds containing at least one of the elements Sr, Ca, Mg, Si, Ge, and Ru.

[0058] According to the present invention, the N 3 The source is selected from compounds containing at least one of the elements Ni, Mn, and Co.

[0059] According to the present invention, the N 4 The source is selected from compounds containing at least one of the elements Cr, Al, V, Nb, Zr, Ti, and Fe.

[0060] In the present invention, the type of the lithium source is not particularly limited, and lithium sources commonly used in this field are, for example, at least one selected from lithium carbonate, lithium hydroxide, lithium fluoride, lithium chloride, lithium nitrate, and lithium acetate.

[0061] In the present invention, the type of the La source is not particularly limited, and may be any compound capable of providing La element that is commonly used in this field.

[0062] In the present invention, the conditions of the first mixing are not particularly limited, and the lithium source, the La source, the N 1 Source, N 2 Source, N 3 source, and said N 4 It is sufficient that the sources are mixed sufficiently and uniformly, and preferably, the conditions of the first mixing include a mixing rotation speed of 400 to 1000 rpm and a mixing time of 3 to 6 hours.

[0063] According to the present invention, the conditions for the first sintering include a sintering temperature of 500 to 1120° C. and a sintering time of 3 to 9 hours.

[0064] In the present invention, a lithium source, a La source, and an optional N 1 Source, any N 2 source, N 3 Source, any N 4 By sintering the first mixture containing the source under the above conditions, a coating having high ionic and electronic conductivity is obtained.

[0065] Furthermore, the conditions for the first sintering include a sintering temperature of 600 to 1000° C. and a sintering time of 3 to 9 hours.

[0066] According to the present invention, the average particle diameter D of the coating agent 50 is 30 to 200 nm.

[0067] In the present invention, the equipment used for crushing is not particularly limited, and the sintered product is crushed using at least one selected from, for example, a fluid mill, a mechanical mill, a colloid mill, a high-energy grinder, a mixing mill, a sand mill, and the like, to obtain the coating agent.

[0068] Furthermore, the average particle diameter D of the coating agent 50 is 50 to 180 nm.

[0069] In the present invention, the conditions of the second mixing are not particularly limited as long as the coating agent and the base material of the positive electrode material can be mixed sufficiently and uniformly, and preferably, the conditions of the second mixing include a mixing rotation speed of 400 to 1000 rpm and a mixing time of 3 to 6 hours.

[0070] In the present invention, the equipment used for the first mixing and the second mixing is not particularly limited, and mixing equipment commonly used in this field, such as a high-speed mixer, may be used.

[0071] According to the present invention, the conditions for the second sintering include a sintering temperature of 300 to 900° C. and a sintering time of 1 to 12 hours.

[0072] In the present invention, when the second mixture is subjected to the second sintering under the above conditions, ion transport properties and electron transport properties are imparted to the surface of the positive electrode material, and excellent electrochemical properties can be imparted to a lithium ion battery including the positive electrode material.

[0073] Further, the conditions for the second sintering include a sintering temperature of 400 to 800° C. and a sintering time of 4 to 10 hours.

[0074] In one particular embodiment of the invention, the coating is prepared by the following steps: (a) Lithium source, La source, optional N 1 Source, any N 2 source, N 3 Source, any N 4 The source is subjected to a fourth mixing to obtain a fourth mixture, and the fourth mixture is subjected to a fourth sintering to crush and obtain a coating.

[0075] In the present invention, the conditions of the fourth mixing are not particularly limited, and the lithium source, the La source, the N 1 Source, N 2 Source, N 3 source, and said N 4The conditions for the fourth mixing may be any conditions as long as the sources can be mixed sufficiently and uniformly, and preferably include a mixing speed of 400 to 1000 rpm and a mixing time of 3 to 6 hours. In the present invention, the conditions for the fourth mixing and the first mixing may be the same or different.

[0076] According to the present invention, the fourth sintering conditions include a sintering temperature of 600 to 1000° C. and a sintering time of 3 to 9 hours.

[0077] Furthermore, the fourth sintering conditions include a sintering temperature of 700 to 1000° C. and a sintering time of 5 to 9 hours.

[0078] In another particular embodiment of the invention, the coating is prepared by the following steps: (b) Lithium source, La source, optional N 1 Source, any N 2 source, N 3 Source, any N 4 The source and the solvent are mixed in a fifth mixture to obtain a fifth mixture, the pH of the fifth mixture is adjusted, and then the fifth sintering is performed after drying and crushing to obtain a coating agent.

[0079] In the present invention, the conditions of the fifth mixing are not particularly limited, and the lithium source, the La source, the N 1 Source, N 2 Source, N 3 Source, N 4 It is sufficient that the source and the solvent are mixed sufficiently and uniformly, and preferably, the fifth mixing conditions include a mixing rotation speed of 400 to 1000 rpm and a mixing time of 3 to 6 hours.

[0080] In the present invention, the type of the solvent is not particularly limited, and the lithium source, the La source, the N 1 Source, N 2 Source, N 3 Source, N 4 The source may be a solution, for example an ethanol solution.

[0081] In the present invention, the pH of the fifth mixture is adjusted with an acidic solution commonly used in this field, such as citric acid, and preferably, an acidic solution is added to adjust the pH value of the fifth mixture to 9 to 12.

[0082] In the present invention, the drying conditions are not particularly limited as long as the fifth mixture can be sufficiently dried, and preferably, the drying conditions include a drying temperature of 40 to 120° C. and a drying time of 5 to 12 hours.

[0083] According to the present invention, the fifth sintering conditions include a sintering temperature of 500 to 850° C. and a sintering time of 4 to 8 hours.

[0084] Further, the conditions of the fifth sintering include a sintering temperature of 550 to 800° C. and a sintering time of 5 to 8 hours.

[0085] A third aspect of the present invention is Lithium source, La source, any N 1 Source, any N 2 source, N 3 Source, any N 4 a source, and a substrate of a cathode material are subjected to a third mixing to obtain a third mixture, and a third sintering is performed to obtain the surface-coated cathode material.

[0086] In the manufacturing method of the surface-coated positive electrode material described in the third aspect of the present invention, the types and amounts of other materials, the conditions and parameters of each step, etc. are all similar to those in the manufacturing method of the second aspect described above, so in order to avoid duplication, in this invention, repeated explanations of some of the characteristics of the materials in the second aspect (e.g., the selectable types of materials, etc.) will be omitted.

[0087] According to the present invention, the lithium source, the La source, the N 1 Source, N 2 Source, N 3 Source, N 4 The amount of sources used is n(Li):n(La):n(N 1 ):n(N 2 ):n(N 3 ):n(N 4) is (α-β-γ-δ):β:γ:δ:(1-λ):λ, where 0.7<α<1.5, 0.2<β<1, 0≦γ<0.5, 0≦δ<0.5, and 0≦λ<0.5.

[0088] According to the present invention, the lithium source, the La source, the N 1 Source, N 2 Source, N 3 Source, N 4 The total amount of the source used is the lithium source by the third sintering, the La source, the N source, and the N 1 source, N 2 source, N 3 source, N 4 The content of the source product is 0.05 to 4 wt%, preferably 0.1 to 3.6 wt%.

[0089] According to the present invention, the conditions for the third sintering include a sintering temperature of 300 to 900° C. and a sintering time of 1 to 12 hours.

[0090] In the present invention, when the third mixture is subjected to a third sintering under the above conditions, the surface of the positive electrode material has ion transport properties and electron transport properties, and excellent electrochemical properties are imparted to a lithium ion battery including the positive electrode material.

[0091] Furthermore, the conditions for the third sintering include a heat treatment temperature of 400 to 800° C. and a heat treatment time of 4 to 10 hours. In the present invention, the average particle diameter D of the substrate of the positive electrode material 50 is 2.3 to 12 μm.

[0092] In the present invention, the substrate of the positive electrode material used in the second and third aspects is not particularly limited and may be produced by a production method commonly used in this field. However, in order to further improve the electrochemical activity of the surface-coated positive electrode material for deintercalating lithium ions and impart excellent rate characteristics to a lithium ion battery including the surface-coated positive electrode material, the substrate of the positive electrode material is preferably produced by the following steps. (1) A nickel salt, a cobalt salt, and a manganese salt are prepared into a mixed salt solution in a molar ratio of n(Ni):n(Co):n(Mn) such that x:y:z. A precipitant and a complexing agent are prepared into a precipitant solution and a complexing agent solution, respectively. (2) The mixed salt solution, the precipitant solution, and the complexing agent solution are fed into a reaction vessel to carry out a coprecipitation reaction to obtain a precursor slurry, which is then subjected to solid-liquid separation, washing, baking, and sieving to obtain a nickel-cobalt-manganese hydroxide precursor. (3) mixing the nickel cobalt manganese hydroxide precursor, a lithium source, and an optional compound containing an M element to obtain a sixth mixture, and subjecting the sixth mixture to a sixth sintering under an oxygen-containing atmosphere, crushing, and sieving to obtain a substrate of the positive electrode material.

[0093] According to the invention, 0≦x≦1, 0≦y≦1, and 0≦z≦1.

[0094] In the present invention, in the method for producing the substrate of the positive electrode material, at least one of the nickel salt, the cobalt salt, the manganese salt, and the compound containing the M element is added.

[0095] In the present invention, the type of nickel salt is not particularly limited, and may be at least one of nickel salts commonly used in this field, such as nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate.

[0096] In the present invention, the type of cobalt salt is not particularly limited, and may be at least one of cobalt salts commonly used in this field, such as cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate.

[0097] In the present invention, the type of manganese salt is not particularly limited, and may be at least one of manganese salts commonly used in this field, such as manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate.

[0098] In the present invention, the type of the precipitating agent is not particularly limited, and may be at least one selected from precipitating agents commonly used in this field, such as ammonium carbonate, ammonium bicarbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium hydroxide, potassium hydroxide, and lithium hydroxide.

[0099] In the present invention, the types of the complexing agent and the second complexing agent are not particularly limited, and are at least one selected from complexing agents commonly used in this field, such as ammonia water, disodium ethylenediaminetetraacetate, ammonium nitrate, ammonium chloride, and ammonium sulfate.

[0100] According to the present invention, the amounts of the nickel cobalt manganese hydroxide precursor, the lithium source, and the compound containing the M element are such that n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)] is 0.95 to 1.5, and n(M) / [n(Ni)+n(Co)+n(Mn)+n(M)] is 0 to 0.06.

[0101] Furthermore, the amounts of the nickel cobalt manganese hydroxide precursor, the lithium source, and the compound containing the M element used are such that n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)] is 0.96 to 1.03, and n(M) / [n(Ni)+n(Co)+n(Mn)+n(M)] is 0 to 0.05.

[0102] According to the present invention, the compound containing the M element is selected from compounds containing at least one of the elements Ga, Sc, In, Y, Ce, Co, La, Cr, Mo, Mn, Fe, Hf, Zr, W, Nb, Sm, and Al.

[0103] In the present invention, the type of the lithium source is not particularly limited, and may be at least one selected from lithium sources commonly used in this field, such as lithium carbonate, lithium hydroxide, lithium fluoride, lithium chloride, lithium nitrate, and lithium acetate.

[0104] According to the present invention, the conditions of the co-precipitation reaction include a reaction temperature of 40-120° C. and a pH value of 9-12.

[0105] In the present invention, the sixth mixing conditions are not particularly limited as long as the nickel-cobalt-manganese hydroxide precursor, the lithium source, and the compound containing the M element are sufficiently and uniformly mixed, and preferably, the sixth mixing conditions include a mixing rotation speed of 400 to 1000 rpm and a mixing time of 3 to 6 hours.

[0106] According to the present invention, the sixth sintering condition includes a sintering temperature of 500 to 1000° C. and a sintering time of 3 to 18 hours.

[0107] In the present invention, when the sixth mixture is subjected to a sixth sintering under the above conditions, the obtained positive electrode material is free of impurity phases.

[0108] Further, the sixth sintering conditions include a sintering temperature of 600 to 1000° C. and a sintering time of 5 to 9 hours.

[0109] A fourth aspect of the present invention provides a surface-coated positive electrode material produced by the above-mentioned production method.

[0110] A fifth aspect of the present invention provides a lithium ion battery comprising the above-mentioned surface-coated positive electrode material.

[0111] In the present invention, the lithium ion battery further includes a negative electrode and an electrolyte. The types of the negative electrode and the electrolyte are not particularly limited, and a common type of negative electrode and electrolyte in this field can be used. For example, the electrolyte is a common commercially available electrolyte, that is, a mixture of equal amounts of LiPF6, ethylene carbonate (EC), and diethyl carbonate (DEC) with a composition of 1 mol / L.

[0112] The present invention will now be described in detail with reference to examples. Average particle size D of the surface-coated positive electrode material 50 is measured by a Malvern particle size analyzer.

[0113] The composition of the surface-coated positive electrode material is calculated from the molar ratio of the reactants.

[0114] The phase structure of the coating and the coated cathode material is measured by XRD.

[0115] The electronic conductivity of the coating is measured by the four-probe method.

[0116] The ionic conductivity of the coating material was calculated by measuring the AC impedance of the blocking electrode using a sintered ceramic sheet and using the formula σ=L / RS, where L is the thickness of the ceramic sheet, R is the impedance value, and S is the area of ​​the effective electrode.

[0117] The oxygen hole formation energies of the coatings are calculated from first principles.

[0118] Assembling a Liquid Button Cell Battery First, the surface-coated positive electrode material, acetylene black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 95:2.5:2.5, coated on aluminum foil, baked, and pressed at a pressure of 100 MPa into a positive electrode plate with a diameter of 12 mm and a thickness of 120 μm. The positive electrode plate was then placed in a vacuum oven and baked at 120°C for 12 hours. The negative electrode is a Li metal plate with a diameter of 17 mm and a thickness of 1 mm, the separator is a polyethylene porous membrane with a thickness of 25 μm, and the electrolyte is a mixture of 1 mol / L LiPF6, ethylene carbonate (EC), and diethyl carbonate (DEC) in equal amounts. The positive plate, separator, negative plate and electrolyte are assembled into a 2025 type button cell in an Ar gas glove box with water and oxygen contents both less than 5 ppm.

[0119] The thermal stability of the surface-coated positive electrode material is measured by performing DSC measurements on the positive plate in the delithiated state (ie, at the cutoff of the battery charge).

[0120] The characteristics of the button battery are evaluated as follows. (1) Charge / discharge characteristic measurement: The charge / discharge characteristics of the material are examined at a temperature of 25°C, in the voltage range of 3.0 to 4.3 V, and at a rate of 0.1 C. (2) Cycle characteristic measurement: After 80 cycles at a temperature of 25°C, a voltage space of 3.0 to 4.3 V, and a rate of 1 C, the capacity retention rate of the material is examined. Manufacturing Example 1

[0121] Cathode material substrate (1) A 2 mol / L mixed salt solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared with a Ni:Co:Mn molar ratio of 93:2:5. A 7 mol / L alkaline sodium hydroxide solution was prepared, and a 4 mol / L ammonia water complexing agent solution was prepared. (2) The mixed salt solution, the alkali solution, and the ammonia water complexing agent solution were continuously added to the stirrer in a confluence manner to react, and the stirring speed was set to 120 rpm. The supply flow rate of the mixed salt solution was controlled at 40 L / h, the supply flow rate of the alkali solution at 20 L / h, the supply flow rate of the complexing agent solution at 7 L / h, the pH at 11.5, and the temperature at 60°C. When the reaction was completed, the obtained nickel cobalt manganese hydroxide slurry was separated into solid and liquid and washed, and the filter cake was baked at 100°C for 10 hours, then sieved, the product was washed with water, and the cake was filtered and dried to obtain the precursor. (3) The above precursor, lithium hydroxide, and aluminum trioxide are uniformly mixed in a ratio of Li / (Ni+Co+Mn+Al)=1.02, Al / (Ni+Co+Mn+Al)=0.01, and sintered at 900°C for 10h. The product is crushed and sieved to obtain an average particle diameter D 50 Thus, a substrate P1 for a positive electrode material having a thickness of 3.4 μm was obtained. Table 1 shows the results of measuring the composition and particle size of the base material of the positive electrode material. Manufacturing Example 2

[0122] (1) A 2 mol / L mixed salt solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared with a molar ratio of Ni, Co, and Mn of 90:3:7. A 7 mol / L alkaline sodium hydroxide solution was prepared, and a 6 mol / L ammonia water complexing agent solution was prepared. (2) The mixed salt solution, the alkali solution, and the ammonia water complexing agent solution were continuously added to the stirrer in a confluence manner to react, and the stirring speed was set to 100 rpm. The supply flow rate of the mixed salt solution was controlled at 35 L / h, the supply flow rate of the alkali solution at 17 L / h, the supply flow rate of the complexing agent solution at 9 L / h, the pH at 11.6, and the temperature at 60°C. When the reaction was completed, the obtained nickel cobalt manganese hydroxide slurry was separated into solid and liquid and washed, and the filter cake was baked at 100°C for 10 h, sieved, the product was washed with water, and the cake was filtered and dried to obtain the precursor. (3) The above precursor, lithium carbonate, and zirconia were uniformly mixed in a ratio of Li / (Ni+Co+Mn+Zr)=1.03 and Zr / (Ni+Co+Mn+Zr)=0.02, sintered at 750°C for 10h, and the product was crushed and sieved to obtain an average particle diameter D 50 The composition and particle size of the positive electrode material substrate P2 were measured and the results are shown in Table 1. Production Example 3

[0123] (1) A 2 mol / L mixed salt solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared with a molar ratio of Ni, Co, and Mn of 90:5:5. A 7 mol / L alkaline sodium hydroxide solution was prepared, and a 5 mol / L ammonia water complexing agent solution was prepared. (2) The mixed salt solution, the alkali solution, and the ammonia water complexing agent solution were continuously added to the stirrer in a confluence manner to react, and the stirring speed was set to 100 rpm. The supply flow rate of the mixed salt solution was controlled at 40 L / h, the supply flow rate of the alkali solution at 19 L / h, the supply flow rate of the complexing agent solution at 9 L / h, the pH at 11.6, and the temperature at 60°C. When the reaction was completed, the obtained nickel cobalt manganese hydroxide slurry was separated into solid and liquid and washed, and the filter cake was baked at 100°C for 10 h, sieved, the product was washed with water, and the cake was filtered and dried to obtain the precursor. (3) The above precursor, lithium carbonate, and zirconia were uniformly mixed in a ratio of Li / (Ni+Co+Mn+Zr)=1.03 and Zr / (Ni+Co+Mn+Zr)=0.02, sintered at 750°C for 10h, and the product was crushed and sieved to obtain an average particle diameter D 50The composition and particle size of the positive electrode material substrate P3 were measured and the results are shown in Table 1.

[0124] [Table 1] Example 1

[0125] S1: Lithium source, La source, N 1 source, N 2 source, N 3 source, N 4 The source was added to a high-speed mixer and stirred at a rotation speed of 1000 rpm for 3 h to obtain a first mixture, which was sintered at 800°C for 8 h in an air atmosphere, cooled to room temperature, crushed, sieved, and used as a coating agent D 50 170nm Li 0.2 La 0.48 Nd 0.1 Sr 0.05 Mn 0.8 Ti 0.2 Got O3. Li by solid phase method 0.2 La 0.48 Nd 0.1 Sr 0.05 Mn 0.8 Ti 0.2 O3 was produced, and the raw materials lithium hydroxide, lanthanum oxide, neodymium oxide, strontium oxide, manganese tetroxide, and titanium dioxide were weighed out according to the weight ratio of each element in the chemical formula. S2: The coating agent and the positive electrode material base material P1 were added to a high-speed mixer and stirred at 800 rpm for 6 h, then sintered at 450°C for 8 h, cooled to room temperature, crushed and sieved to obtain a surface-coated positive electrode material A1, where the amount of the coating agent used was 3 wt% based on the total weight of the positive electrode material base material P1. The types, amounts of each material used, and specific operating conditions are shown in Table 2. The XRD spectrum of the coating agent is shown in Figure 1, and as can be seen from Figure 1, the characteristic peak at 31°-35° shows a bimodal distribution. The XRD spectrum of the surface-coated positive electrode material A1 is shown in Figure 2, and as can be seen from Figure 2, after coating, the double peak belonging to the coating agent still exists at 31°-35°. According to the XRD spectra of the coating material and the surface-coated cathode material, the peak intensity of the minor peak I in the bimodal distribution of the characteristic peak at 31° to 35° for the coating material is b and the peak intensity of the main peak I a Comparison with I b / I a , coating layer Li 0.2 La 0.48 Nd 0.1 Sr 0.05 Mn 0.8 Ti 0.2 Peak intensity of the main peak between 31° and 35° of O3 I a Peak intensity I of the (003) crystal plane of the substrate P1 of the positive electrode material (003) Comparison with I a / I (003) , coating layer Li 0.2 La 0.48 Nd 0.1 Sr 0.05 Mn 0.8 Ti 0.2 Peak area A of the main peak between 31° and 35° of O3 a and the peak area A of the (003) crystal plane of the positive electrode material substrate P (003) Ratio to A a / A (003) The calculation results are shown in Table 3. The results of measuring the particle size, ionic conductivity, electronic conductivity, and oxygen hole formation energy of the coating agent are shown in Table 3. The results of XRD measurement of the coating agent, the substrate of the positive electrode material, and the surface-coated positive electrode material are shown in Table 3. Example 2

[0126] S1: Lithium source, La source, N 1 source, N 2 source, N 3 The raw materials were added to a high-speed mixer and stirred at 1200 rpm for 2 h, then sintered at 750 °C for 6 h in air, cooled to room temperature, crushed, sieved, and filtered to obtain D50 200nm coating Li 0.34 La 0.47 Ce 0.05 Mg 0.05 MnO3 was obtained. Li by solid phase method 0.34 La 0.47 Ce 0.05 Mg 0.05 MnO3 is produced and, according to the weight ratio of each element in the chemical formula, lithium carbonate, lanthanum oxide, cerium oxide (N 1 source), magnesium oxide (N 2 source), Manganous oxide (N 3 The source was weighed. S2: The coating agent and the cathode material base material P2 were added to a high-speed mixer and stirred at 950 rpm for 4 h, then sintered at 500°C for 5 h, cooled to room temperature, crushed and sieved to obtain the surface-coated cathode material A2, where the amount of the coating agent used was 1.5 wt% based on the total weight of the cathode material base material P2. The types, amounts of each material used, and specific operating conditions are shown in Table 2. According to the XRD spectra of the coating material and the surface-coated cathode material, the peak intensity of the minor peak I in the bimodal distribution of the characteristic peak at 31° to 35° for the coating material is b and the peak intensity of the main peak I a Comparison with I b / I a , coating layer Li 0.34 La 0.47 Ce 0.05 Mg 0.05 Peak intensity of the main peak of MnO3 between 31° and 35° I a and the peak intensity I of the (003) crystal plane of the positive electrode material substrate P2 (003) Comparison with I a / I (003) , coating layer Li 0.34 La 0.47 Ce 0.05 Mg 0.05 Peak area A of the main peak of MnO3 between 31° and 35° a and the peak area A of the (003) crystal plane of the positive electrode material substrate P (003) Ratio to A a / A (003)The calculation results are shown in Table 3. The results of measuring the particle size, ionic conductivity, electronic conductivity, and oxygen hole formation energy of the coating agent are shown in Table 3. The results of XRD measurement of the coating agent, the substrate of the positive electrode material, and the surface-coated positive electrode material are shown in Table 3. Example 3

[0127] S1: Lithium source, La source, N 1 source, N 3 source, N 4 The source material was added to a high-speed mixer and stirred at a rotation speed of 1000 rpm for 3 h to obtain a first mixture, which was then sintered at 800°C for 8 h in an air atmosphere, cooled to room temperature, crushed, sieved, and filtered to obtain D 50 110nm coating Li 0.5 La 0.4 Sm 0.2 Ni 0.7 Cr 0.3 Got O3. Li by solid phase method 0.5 La 0.4 Sm 0.2 Ni 0.7 Cr 0.3 O3 is produced, and lithium carbonate, lanthanum oxide, samarium oxide (N 1 source), Nickel oxide (N 3 source), chromium trioxide (N 4 The source was weighed. S2: The coating agent and the cathode material base material P2 were added to a high-speed mixer and stirred at 800 rpm for 4 h, then sintered at 500°C for 8 h, cooled to room temperature, crushed and sieved to obtain surface-coated cathode material A3, where the amount of the coating agent used was 2.2 wt% based on the total weight of the cathode material base material P2. The types, amounts of each material used, and specific operating conditions are shown in Table 2. According to the XRD spectra of the coating material and the surface-coated cathode material, the peak intensity of the minor peak I in the bimodal distribution of the characteristic peak at 31° to 35° for the coating material is b and the peak intensity of the main peak I a Comparison with I b / I a , coating layer Li0.5 La 0.4 Sm 0.2 Ni 0.7 Cr 0.3 Peak intensity of the main peak between 31° and 35° of O3 I a and the peak intensity I of the (003) crystal plane of the positive electrode material substrate P2 (003) Comparison with I a / I (003) , coating layer Li 0.5 La 0.4 Sm 0.2 Ni 0.7 Cr 0.3 Peak area A of the main peak between 31° and 35° of O3 a and the peak area A of the (003) crystal plane of the positive electrode material substrate P (003) Ratio to A a / A (003) The calculation results are shown in Table 3. The results of measuring the particle size, ionic conductivity, electronic conductivity, and oxygen hole formation energy of the coating agent are shown in Table 3. The results of XRD measurement of the coating agent, the substrate of the positive electrode material, and the surface-coated positive electrode material are shown in Table 3. Example 4

[0128] S1: Lithium source, La source, N 1 source, N 2 source, N 3 source, N 4 The source and ethanol solution were mixed, and then citric acid was added to the above solution to form a mixed solution with pH=9.6, which was stirred at 60°C and 500 rpm for 5 h, transferred to an oven at 120°C for 8 h, sintered at 800°C for 8 h in air atmosphere, cooled to room temperature, crushed, sieved, and then filtered to obtain the D 50 A coating of 80 nm was obtained. Li by sol-gel method 0.43 La 0.48 Pr 0.08 Ca 0.1 Mn 0.7 Fe 0.3 O3 is produced, and lithium nitrate, lanthanum nitrate, praseodymium chloride (N 1 source), calcium chloride (N 2 source), manganese chloride (N 3 source), ferric chloride (N4 The source was weighed. S2: The coating agent and the cathode material base material P1 were added to a high-speed mixer and stirred at 800 rpm for 6 h, then sintered at 450°C for 8 h, cooled to room temperature, crushed and sieved to obtain surface-coated cathode material A4, where the amount of the coating agent used was 0.8 wt% based on the total weight of the cathode material base material P1. The types, amounts of each material used, and specific operating conditions are shown in Table 2. According to the XRD spectra of the coating material and the surface-coated cathode material, the peak intensity of the minor peak I in the bimodal distribution of the characteristic peak at 31° to 35° for the coating material is b and the peak intensity of the main peak I a Comparison with I b / I a , coating layer Li 0.43 La 0.48 Pr 0.08 Ca 0.1 Mn 0.7 Fe 0.3 Peak intensity of the main peak between 31° and 35° of O3 I a and the peak intensity I of the (003) crystal plane of the positive electrode material substrate P1 (003) Comparison with I a / I (003) , coating layer Li 0.43 La 0.48 Pr 0.08 Ca 0.1 Mn 0.7 Fe 0.3 Peak area A of the main peak between 31° and 35° of O3 a and the peak area A of the (003) crystal plane of the positive electrode material substrate P (003) Ratio to A a / A (003) The calculation results are shown in Table 3. The results of measuring the particle size, ionic conductivity, electronic conductivity, and oxygen hole formation energy of the coating agent are shown in Table 3. The results of XRD measurement of the coating agent, the substrate of the positive electrode material, and the surface-coated positive electrode material are shown in Table 3. Example 5

[0129] S1: Lithium source, La source, N 1 source, N 2 source, N3 source, N 4 The source was added to a high-speed mixer and stirred at a rotation speed of 1000 rpm for 3 h to obtain a first mixture, which was sintered at 800°C for 8 h in an air atmosphere, cooled to room temperature, crushed, sieved, and used as a coating agent D 50 110nm Li 0.5 La 0.4 Sm 0.2 Ni 0.7 Cr 0.3 Got O3. Li by solid phase method 0.5 La 0.4 Sm 0.2 Ni 0.7 Cr 0.3 O3 is produced, and lithium carbonate, lanthanum oxide, samarium oxide (N 1 source), Nickel oxide (N 3 source), chromium trioxide (N 4 The source was weighed. S2: The coating agent and the cathode material base material P2 were added to a high-speed mixer and stirred at 800 rpm for 4 h, then sintered at 500°C for 8 h, cooled to room temperature, crushed and sieved to obtain surface-coated cathode material A5, where the amount of the coating agent used was 0.2 wt% based on the total weight of the cathode material base material P2. The types, amounts of each material used, and specific operating conditions are shown in Table 2. The XRD spectra of the coating and the surface-coated cathode material show a bimodal distribution of characteristic peaks at 31°-35° for the coating, with a minor peak intensity I b and the peak intensity of the main peak I a Comparison with I b / I a , coating layer Li 0.5 La 0.4 Sm 0.2 Ni 0.7 Cr 0.3 Peak intensity of the main peak between 31° and 35° of O3 I a and the peak intensity I of the (003) crystal plane of the positive electrode material substrate P2 (003) Comparison with I a / I (003) , coating layer Li 0.5 La 0.4Sm 0.2 Ni 0.7 Cr 0.3 Main peak area A between 31° and 35° of O3 a and the peak area A of the (003) crystal plane of the positive electrode material substrate P (003) Ratio to A a / A (003) The calculation results are shown in Table 3. The results of measuring the particle size, ionic conductivity, electronic conductivity, and oxygen hole formation energy of the coating agent are shown in Table 3. The results of XRD measurement of the coating agent, the substrate of the positive electrode material, and the surface-coated positive electrode material are shown in Table 3. Example 6

[0130] S1: Lithium source, La source, N 1 source, N 2 source, N 3 source, N 4 The source was added to a high-speed mixer and stirred at a rotation speed of 1000 rpm for 3 h to obtain a first mixture, which was sintered at 900°C for 8 h in an air atmosphere, cooled to room temperature, crushed, sieved, and used as a coating agent D 50 220nm Li 0.2 La 0.48 Nd 0.1 Sr 0.05 Mn 0.8 Ti 0.2 Got O3. Li by solid phase method 0.2 La 0.48 Nd 0.1 Sr 0.05 Mn 0.8 Ti 0.2 O3 is produced, and lithium hydroxide, lanthanum oxide, neodymium oxide (N 1 source), strontium oxide (N 2 source), Manganous oxide (N 3 source), titanium dioxide (N 4 The source was weighed. S2: The coating agent and the cathode material base material P3 were added to a high-speed mixer and stirred at 800 rpm for 6 h, then sintered at 300°C for 8 h, cooled to room temperature, crushed and sieved to obtain surface-coated cathode material A6, where the amount of the coating agent used was 8 wt% based on the total weight of the cathode material base material P3. The types, amounts of each material used, and specific operating conditions are shown in Table 2. According to the XRD spectra of the coating material and the surface-coated cathode material, the peak intensity of the minor peak I in the bimodal distribution of the characteristic peak at 31° to 35° for the coating material is b and the peak intensity of the main peak I a Comparison with I b / I a , coating layer Li 0.2 La 0.48 Nd 0.1 Sr 0.05 Mn 0.8 Ti 0.2 Main peak intensity between 31° and 35° of O3 I a and the peak intensity I of the (003) crystal plane of the positive electrode material substrate P3 (003) Comparison with I a / I (003) , coating layer Li 0.2 La 0.48 Nd 0.1 Sr 0.05 Mn 0.8 Ti 0.2 Peak area A of the main peak between 31° and 35° of O3 a and the peak area A of the (003) crystal plane of the positive electrode material substrate P (003) Ratio to A a / A (003) The calculation results are shown in Table 3. The results of measuring the particle size, ionic conductivity, electronic conductivity, and oxygen hole formation energy of the coating agent are shown in Table 3. The results of XRD measurement of the coating agent, the substrate of the positive electrode material, and the surface-coated positive electrode material are shown in Table 3. Comparative Example 1

[0131] The substrate P1 of the positive electrode material produced in Production Example 1 was used as positive electrode material D1. Table 3 shows the results of XRD measurement of positive electrode material D1. Comparative Example 2

[0132] The substrate P2 of the positive electrode material produced in Production Example 2 was used as positive electrode material D2. Table 3 shows the results of XRD measurement of positive electrode material D2. Comparative Example 3

[0133] The substrate P3 of the positive electrode material produced in Production Example 3 was used as positive electrode material D3. The results of XRD measurement of positive electrode material D3 are shown in Table 3.

[0134] [Table 2]

[0135] Table 3 [Table 3-1]

[0136] Table 3 (continued) [Table 3-2] Measurement example

[0137] The positive electrode materials of the examples and comparative examples were assembled into lithium ion batteries, and the thermal stability of the positive electrode materials in a delithiated state was measured. The results are shown in Table 4. The characteristics of the lithium ion batteries were measured and the results are shown in Table 5.

[0138] [Table 4]

[0139] [Table 5]

[0140] As can be seen from Tables 4 and 5, the positive electrode materials produced in Examples 1 to 6 have higher temperatures corresponding to the DSC peaks after complete delithiation compared to Comparative Examples 1 to 3, which reveals that the positive electrode materials of Examples 1 to 6 have better thermal stability. In addition, both the rate characteristics and cycle characteristics of the lithium ion batteries assembled using the positive electrode materials produced in Examples 1 to 6 are improved.

[0141] 5, the positive electrode material of Example 1 has a DSC peak position in a completely delithiated state at 210° C., the positive electrode material of Example 4 has a DSC peak position in a completely delithiated state at 207° C., and the positive electrode material of Comparative Example 1 has a DSC peak position in a completely delithiated state at 203° C. This shows that the positive electrode materials of Examples 1 and 4 have better thermal stability than Comparative Example 1.

[0142] As shown in FIG. 3, in Examples 1 and 4, the discharge capacity at each rate was improved compared to Comparative Example 1. This proves that the coating improves the rate characteristics, shifts the DSC peak position backward, and improves the thermal stability of the material.

[0143] 6, the positive electrode material of Example 2 has a DSC peak position in a completely delithiated state at 218° C., the positive electrode material of Example 3 has a DSC peak position in a completely delithiated state at 213° C., and the positive electrode material of Comparative Example 2 has a DSC peak position in a completely delithiated state at 205° C. This shows that the positive electrode materials of Examples 2 and 3 have better thermal stability than Comparative Example 2.

[0144] 4, in Example 2 and Example 3, the cycle retention rate was improved compared to Comparative Example 2, proving that the coating reduced side reactions between the positive electrode material and the electrolyte. The DSC peak position was also increased, proving the improvement of the thermal stability of the material itself.

Claims

1. A surface-coated positive electrode material, A substrate and a coating layer coated on a surface of the substrate, The coating layer was subjected to XRD measurement. The characteristic peak at 2θ of 31° to 35° exhibited a bimodal distribution, and the peak intensity I b and the peak intensity of the main peak I a Comparison with I b / I a is 0.8 to 1, The coating layer has a composition represented by formula II. Li α-β-γ-δ La β N 1 γ N 2 δ N 3 1-λ N 4 λ O 3 Formula II (wherein 0.7<α<1.5, 0.2<β<1, 0≦γ<0.5, 0≦δ<0.5, 0≦λ<0.5, N 1 is at least one element selected from Y, Nd, Pr, Ce, Sm, and Sc, N 2 is at least one element selected from Sr, Ca, Mg, Si, Ge, and Ru, N 3 is at least one element selected from Ni, Mn, and Co, and N 4 is at least one element selected from Cr, Al, V, Nb, Zr, Ti, and Fe.)

2. The substrate was subjected to XRD measurement. The peak intensity of the characteristic peak (003) corresponding to the (003) crystal plane was determined as I (003) Then, 0.01%≦I a / I (003) × 100%≦3.5%, The substrate was subjected to XRD measurement. The peak area of ​​the characteristic peak (003) corresponding to the (003) crystal plane was determined as A (003) The coating layer was subjected to XRD measurement, and the peak area of ​​the main peak in the characteristic bimodal distribution where 2θ is 31° to 35° was determined as A a Then, 0.01%≦A a / A (003) 2. The surface-coated positive electrode material according to claim 1, wherein x 100%≦6%.

3. 2. The surface-coated positive electrode material of claim 1, wherein the substrate has a composition shown in Formula I: Li 1+a Ni x Co y Mn z M k O 2 Formula I (Note that -0.05≦a≦0.5, 0≦x≦1, 0≦y≦1, 0≦z≦1, 0≦k≦0.06, and 0<x+y+z+k≦1, and M is at least one element selected from Ga, Sc, In, Y, Ce, Co, La, Cr, Mo, Mn, Fe, Hf, Zr, W, Nb, Sm, and Al.)

4. In formula I, M is at least one element selected from Ce, Co, La, Cr, Mo, Y, Zr, W, Nb, and Al; In formula II, 0.9<α<1.3, 0.35<β<0.7, 0.04≦γ<0.4, 0<δ<0.3, and 0≦λ<0.46; In formula II, N 1 is at least one element selected from Nd, Pr, Ce, Sm, and Sc; In formula II, N 2 is at least one element selected from Sr, Ca, Mg, Si, and Ru; In formula II, N 3 is selected from Ni and / or Mn; In formula II, N 4 is at least one element selected from Cr, Al, Nb, Zr, Ti, and Fe; The surface-coated positive electrode material according to claim 3, wherein the content of the coating layer is 0.05 to 4 wt % based on the total weight of the substrate.

5. The average particle diameter D of the surface-coated positive electrode material 50 is 2 to 17 μm, The electronic conductivity of the coating layer is 1×10 -5 S / cm to 8 x 10 -3 S / cm, The ionic conductivity of the coating layer is 1×10 -6 S / cm to 6 x 10 -4 S / cm, 2. The surface-coated positive electrode material according to claim 1, wherein the oxygen hole formation energy of the coating layer is −2 eV to 4.5 eV.

6. 2. The surface-coated positive electrode material according to claim 1, wherein T1 is a temperature corresponding to a heat dissipation peak obtained by DSC measurement of the surface-coated positive electrode material, and T0 is a temperature corresponding to a heat dissipation peak obtained by DSC measurement of the base material, and T1-T0 is 3 to 15° C.

7. A method for producing a surface-coated positive electrode material, comprising the steps of: Lithium source, La source, optional N 1 Source, any N 2 source, N 3 Source, any N 4 S1, subjecting the source to a first mixing to obtain a first mixture, and subjecting the first mixture to a first sintering to crush and obtain a coating; and (S2) subjecting the coating agent and the substrate of the cathode material to a second mixing to obtain a second mixture, and subjecting the second mixture to a second sintering to obtain the surface-coated cathode material; The lithium source, the La source, the N 1 Source, said N 2 Source, said N 3 Source, said N 4 The amount of the source used is n(Li):n(La):n(N 1 ): n (N 2 ): n (N 3 ): n (N 4 ) is (α-β-γ-δ):β:γ:δ:(1-λ):λ, where 0.7<α<1.5, 0.2<β<1, 0≦γ<0.5, 0≦δ<0.5, and 0≦λ<0.5; 2. The method for producing a surface-coated positive electrode material according to claim 1, wherein the amount of the coating agent used is 0.05 to 4 wt % based on the total weight of the base material of the positive electrode material.

8. A method for producing a surface-coated positive electrode material, comprising the steps of: Lithium source, La source, optional N 1 Source, any N 2 source, N 3 Source, any N 4 subjecting the source and the substrate of the positive electrode material to a third mixture to obtain a third mixture, and performing a third sintering to obtain the surface-coated positive electrode material; The lithium source, the La source, the N 1 Source, said N 2 Source, said N 3 Source, said N 4 The amount of the source used is n(Li):n(La):n(N 1 ): n (N 2 ): n (N 3 ): n (N 4 ) is (α-β-γ-δ):β:γ:δ:(1-λ):λ, where 0.7<α<1.5, 0.2<β<1, 0≦γ<0.5, 0≦δ<0.5, and 0≦λ<0.5; The lithium source, the La source, the N 1 Source, said N 2 Source, said N 3 Source, said N 4 The total amount of the source used is the lithium source by the third sintering, the La source, the N source, and the N source based on the total weight of the base material of the positive electrode material. 1 source, N 2 source, N 3 source, N 4 The method for producing a surface-coated positive electrode material according to claim 1, characterized in that the content of the source product is 0.05-4 wt %.

9. The N 1 The source is selected from compounds containing at least one of the elements Y, Nd, Pr, Ce, Sm, and Sc; The N 2 The source is selected from compounds containing at least one of the elements Sr, Ca, Mg, Si, Ge, and Ru; The N 3 The source is selected from compounds containing at least one of the elements Ni, Mn, and Co; The N 4 The source is selected from compounds containing at least one of the elements Cr, Al, V, Nb, Zr, Ti, and Fe; The conditions of the first sintering include a sintering temperature of 500 to 1120° C. and a sintering time of 3 to 9 h; The average particle diameter D of the coating agent 50 is 30 to 200 nm, The manufacturing method according to claim 7, wherein the conditions of the second sintering include a sintering temperature of 300 to 900° C. and a sintering time of 1 to 12 h.

10. The N 1 The source is selected from compounds containing at least one of the elements Y, Nd, Pr, Ce, Sm, and Sc; The N 2 The source is selected from compounds containing at least one of the elements Sr, Ca, Mg, Si, Ge, and Ru; The N 3 The source is selected from compounds containing at least one of the elements Ni, Mn, and Co; The N 4 The source is selected from compounds containing at least one of the elements Cr, Al, V, Nb, Zr, Ti, and Fe; The manufacturing method according to claim 8, wherein the conditions of the third sintering include a sintering temperature of 300 to 900° C. and a sintering time of 1 to 12 h.

11. The step S1 (a) A lithium source, a La source, and optionally N 1 Source, any N 2 source, N 3 Source, any N 4 subjecting the source to a fourth mixing to obtain a fourth mixture, and subjecting the fourth mixture to a fourth sintering to crush and obtain a coating; or (b) A lithium source, a La source, and optionally N 1 Source, any N 2 source, N 3 Source, any N 4 subjecting the source and the solvent to a fifth mixture to obtain a fifth mixture, adjusting the pH of the fifth mixture, and then drying and performing a fifth sintering and crushing to obtain a coating agent; The fourth sintering conditions include a sintering temperature of 600 to 1000° C. and a sintering time of 3 to 9 h; The manufacturing method according to claim 7, wherein the fifth sintering conditions include a sintering temperature of 500 to 850° C. and a sintering time of 4 to 8 h.

12. The substrate of the positive electrode material is (1) preparing a mixed salt solution of nickel salt, cobalt salt, and manganese salt in a molar ratio of n(Ni):n(Co):n(Mn)=x:y:z, and preparing a precipitant and a complexing agent in a precipitant solution and a complexing agent solution, respectively; (2) feeding the mixed salt solution, the precipitant solution, and the complexing agent solution into a reactor to carry out a coprecipitation reaction to obtain a precursor slurry, and then subjecting the precursor slurry to solid-liquid separation, washing, baking, and sieving to obtain a nickel-cobalt-manganese hydroxide precursor; (3) mixing the nickel cobalt manganese hydroxide precursor, a lithium source, and an optional compound containing an M element to obtain a sixth mixture, and subjecting the sixth mixture to a sixth sintering under an oxygen-containing atmosphere, followed by crushing and sieving to obtain a substrate of the positive electrode material; 0≦x≦1, 0≦y≦1, 0≦z≦1, The amounts of the nickel cobalt manganese hydroxide precursor, the lithium source, and the compound containing the M element used are such that n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)] is 0.95 to 1.5, and n(M) / [n(Ni)+n(Co)+n(Mn)+n(M)] is 0 to 0.06, The compound containing the M element is selected from compounds containing at least one element selected from Ga, Sc, In, Y, Ce, Co, La, Cr, Mo, Mn, Fe, Hf, Zr, W, Nb, Sm, and Al; The conditions of the coprecipitation reaction include a reaction temperature of 40 to 120° C. and a pH value of 9 to 12; The manufacturing method according to claim 7, wherein the sixth sintering conditions include a sintering temperature of 500 to 1000° C. and a sintering time of 3 to 18 h.

13. The substrate of the positive electrode material is (1) preparing a mixed salt solution of nickel salt, cobalt salt, and manganese salt in a molar ratio of n(Ni):n(Co):n(Mn)=x:y:z, and preparing a precipitant and a complexing agent in a precipitant solution and a complexing agent solution, respectively; (2) feeding the mixed salt solution, the precipitant solution, and the complexing agent solution into a reactor to carry out a coprecipitation reaction to obtain a precursor slurry, and then subjecting the precursor slurry to solid-liquid separation, washing, baking, and sieving to obtain a nickel-cobalt-manganese hydroxide precursor; (3) mixing the nickel cobalt manganese hydroxide precursor, a lithium source, and an optional compound containing an M element to obtain a sixth mixture, and subjecting the sixth mixture to a sixth sintering under an oxygen-containing atmosphere, followed by crushing and sieving to obtain a substrate of the positive electrode material; 0≦x≦1, 0≦y≦1, 0≦z≦1, The amounts of the nickel cobalt manganese hydroxide precursor, the lithium source, and the compound containing the M element used are such that n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)] is 0.95 to 1.5, and n(M) / [n(Ni)+n(Co)+n(Mn)+n(M)] is 0 to 0.06, The compound containing the M element is selected from compounds containing at least one element selected from Ga, Sc, In, Y, Ce, Co, La, Cr, Mo, Mn, Fe, Hf, Zr, W, Nb, Sm, and Al; The conditions of the coprecipitation reaction include a reaction temperature of 40 to 120° C. and a pH value of 9 to 12; The manufacturing method according to claim 8, wherein the sixth sintering conditions include a sintering temperature of 500 to 1000° C. and a sintering time of 3 to 18 h.

14. 1. A lithium ion battery, A lithium ion battery comprising the surface-coated positive electrode material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Doped and coated dual-modified lithium / sodium layered metal oxide positive electrode material and one-step synthesis method therefor

    CN107369826A

  • Lithium niobate and manufacturing method thereof

    JP2020035607A

  • Positive electrode material for all-solid-state battery, all-solid-state battery, and manufacturing method of positive-electrode active material for all-solid-state battery

    JP2020113376A